Identifying Major Factors That Motivate Students Volunteer In A Non-Profit Organization: A Case Study At PAS-ITB (Pembinaan Anak-Anak Salman - Institut Teknologi Bandung) - Dwiyanti, Natalia; Pritasari, Adita (Journal of Business and Management, 2020)
Pembinaan Anak-Anak Salman - Institut Teknologi Bandung – also known as PAS-ITB – is one of many nonprofit organizations in Bandung. PAS-ITB has established in 1982 and engaged in the field related to children education. Since 10 years after it was formed, PAS-ITB cannot accept all participants because it considers that participation from volunteers is still lacking. It can be seen from the less interest and high turnover. For this research, researcher uses the qualitative research method which data is gained through a semi-structured interview and participative observation. The result will be analyzed using coding method. The interview was done by interviewing 15 informants that consist of active members, alumnus, and ex- members. Researcher use motivation factors in non profit organization as the framework of the interview. The factors that influence to increase member motivation are altruism, egoism, reward, social relationship, leisure, and career development. The research, proven that six of the motivation factors in non profit organization exist in PAS-ITB. This research also found new factors that influence member motivation to join non profit organization, especially in PAS-ITB. These factors are belief, creative environment, leadership style, manage organization, motivated environment, organization rule, and distance. After the researcher interpreted the data, it can know that the dominant factors that influence member motivation in PAS-ITB are egoistic motivation, social relationship motivation, career development motivation, leisure motivation and organization rule. By known the dominant factors that influence motivation in PAS-ITB, directors can make programs that support member needs as their factors.